Layered composite material, process for its preparation and use as catalyst
Patent Information
- Application Number
- CN202211560330.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-07
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-12-07
AI Technical Summary
[0005]针对目前公开的燃烧催化剂耐硫化氢性能不佳、稳定性不好等特点,本发明提出一种净化含硫化氢VOCs气体的催化剂及制备方法
[0126]本发明的含硫化氢VOCs气体净化催化剂,在较高的空速条件下,具有高的催化活性和稳定性;
Smart Images

Figure SMS_1 
Figure HDA0003984424370000011 
Figure HDA0003984424370000012
Abstract
Description
Technical Field
[0001] This invention relates to a layered composite material, its preparation method, and its application as a catalyst, belonging to the field of catalytic combustion environmental protection. Background Technology
[0002] Since the beginning of the 21st century, the environmental situation has become increasingly severe, with air pollution being a particularly prominent problem. Following PM2.5, SO2, and NO... x After pollutants are brought under control, the prevention and control of volatile organic compounds (VOCs) becomes the focus of air pollution control. However, air pollution in my country is characterized by regional and complex pollution patterns. The interaction between VOCs and other air pollutants can induce ozone and photochemical smog. Furthermore, VOCs are characterized by their irritant properties, high toxicity, persistence, and photochemical reactivity, causing serious impacts on human survival and the natural environment. Sulfur-containing VOCs, in particular, pose a significant environmental risk, making their control increasingly urgent. Currently, domestic and international emission standards for VOCs are continuously improving. The key to improving my country's atmospheric environment is to comprehensively promote VOCs emission control in areas with severe complex air pollution.
[0003] Currently, VOCs removal technologies mainly include adsorption, direct combustion, low-temperature plasma, and catalytic combustion. Among these, catalytic combustion is considered one of the most promising technologies for VOCs control due to its advantages such as low ignition temperature, high treatment efficiency, and low likelihood of generating secondary pollution. However, for combustion catalysts containing hydrogen sulfide, the active sites are easily corroded by sulfur during the catalytic reaction, leading to catalyst deactivation. Hydrogen sulfide not only competes with VOCs molecules for adsorption active sites but also reacts with catalyst components to oxidize and form sulfates that cover the catalyst surface, damaging the catalyst structure, reducing active sites, causing catalyst poisoning, and inhibiting catalytic activity. Therefore, there is an urgent need to develop combustion catalysts with excellent sulfur resistance. Chinese patent CN105709854A discloses a metal-based catalytic combustion catalyst and its preparation method. However, the metal-based catalyst cannot operate stably for extended periods under high water vapor and high SO2 conditions. Chinese patent CN89105594.0 discloses a "catalyst for incinerating sulfur-containing organic waste gas and its preparation method." This catalyst uses natural mordenite zeolite treated with sulfuric acid as a carrier, V₂O₅ as the active component, and precious metals such as platinum and palladium as auxiliary agents. This catalyst has a good effect on the oxidation of sulfur-containing organic matter and also has a good purification effect on CO, low-carbon alkanes, and oxygen-containing organic matter. Chinese patent CN102553585A discloses a sulfur-resistant catalyst for deoxygenating gas, its preparation method, and its application. Mo is added to the catalyst, and pre-sulfurization is required to ensure the catalyst's sulfur resistance; however, the catalyst's activity is not high. Summary of the Invention
[0004] Therefore, the purpose of this invention is to provide a combustion catalyst with simple preparation process, high catalytic activity, and resistance to hydrogen sulfide, and the same preparation method.
[0005] In view of the poor hydrogen sulfide resistance and instability of currently disclosed combustion catalysts, this invention proposes a catalyst for purifying hydrogen sulfide-containing VOCs gas and its preparation method.
[0006] According to one aspect of this application, a layered composite material is provided, the layered composite material comprising a honeycomb carrier, a coating I coated on a substrate surface, and a coating II coated on the surface of the coating I;
[0007] The coating I contains a metal oxide carrier, a noble metal element, and additives;
[0008] The coating II includes region a and region b;
[0009] The coating in region a is region a coating;
[0010] The coating in region b is the region b coating;
[0011] The coating in region a contains a metal oxide carrier and a transition metal oxide;
[0012] The coating in region b contains a metal oxide carrier, a transition metal oxide, and a noble metal element.
[0013] The mass of coating I is 3 to 15 wt% of the mass of the cellular carrier;
[0014] Optionally, the mass of the coating I is any value among 3wt%, 5wt%, 10wt%, and 15wt% of the mass of the cellular carrier, or a range between any two.
[0015] The mass of the coating in region a is 1.5 to 10 wt% of the mass of the cellular carrier;
[0016] Optionally, the mass of the coating in region a is any value among 1.5wt%, 2wt%, 5wt%, and 10wt% of the mass of the cellular carrier, or a range between any two.
[0017] The mass of the coating in region b is 1.5 to 10 wt% of the mass of the cellular carrier.
[0018] Optionally, the mass of the coating in region b is any value among 1.5 wt%, 2 wt%, 5 wt%, and 10 wt% of the mass of the cellular carrier, or a range between any two.
[0019] The metal oxide support is selected from at least one of aluminum oxide, titanium oxide, cerium oxide, zirconium oxide, yttrium oxide, neodymium oxide, tin oxide, and chromium oxide;
[0020] The precious metal element is selected from at least one of platinum, palladium, osmium, iridium, ruthenium, and rhodium;
[0021] The auxiliary agent is selected from at least one of cobalt oxide, lanthanum oxide, potassium oxide, barium oxide, tin oxide, calcium oxide, and zinc oxide;
[0022] The transition metal oxide is selected from at least one of iron oxide, cobalt oxide, molybdenum oxide, tin oxide, chromium oxide, copper oxide, nickel oxide, manganese oxide, vanadium oxide, and tungsten oxide.
[0023] In coating I:
[0024] The mass content of the metal oxide support is 90–99.6 wt%.
[0025] Optionally, the mass content of the metal oxide support is any value among 90wt%, 95wt%, and 99.6wt%, or any range between two of them.
[0026] The mass content of the precious metal element is 0.3 to 10 wt%.
[0027] Optionally, the mass content of the precious metal element is any value among 0.3wt%, 1wt%, 5wt%, and 10wt%, or a range between any two.
[0028] The mass content of the auxiliary agent is 0.1-3 wt%.
[0029] Optionally, the mass content of the additive is any value from 0.1wt%, 1wt%, 2wt%, 3wt%, or any range between two of them.
[0030] In the coating of region a:
[0031] The mass content of the metal oxide support is 80–99.5 wt%.
[0032] Optionally, the mass content of the metal oxide support is any value among 80wt%, 85wt%, 90wt%, 95wt%, and 99.5wt%, or a range between any two.
[0033] The mass content of the transition metal oxide is 0.5–20 wt%.
[0034] Optionally, the mass content of the transition metal oxide is any value from 0.5wt%, 1wt%, 5wt%, 10wt%, 15wt%, 20wt%, or any range between two.
[0035] The coating in region b:
[0036] The mass content of the metal oxide carrier is 70-99 wt%;
[0037] Optionally, the mass content of the metal oxide support is any value among 70wt%, 75wt%, 80wt%, 85wt%, 90wt%, 95wt%, and 99wt%, or a range between any two.
[0038] The mass content of the transition metal oxide is 0.5–20 wt%.
[0039] Optionally, the mass content of the transition metal oxide is any value from 0.5wt%, 1wt%, 5wt%, 10wt%, 15wt%, 20wt%, or any range between both.
[0040] The mass content of the precious metal element is 0.5 to 10 wt%.
[0041] Optionally, the mass content of the precious metal element is any value among 0.5wt%, 1wt%, 5wt%, and 10wt%, or a range between any two.
[0042] According to another aspect of this application, a method for preparing the above-mentioned layered composite material is provided, comprising the following steps:
[0043] 1) Obtain coating I with paint X;
[0044] 2) Obtain the coating Y of region a;
[0045] 3) Obtain the coating Z of region b;
[0046] 4) Prepare coating slurry x, coating slurry y, and coating slurry z from coatings X, Y, and Z;
[0047] 5) Coating is performed on a honeycomb carrier, followed by calcination and reduction to obtain the layered composite material.
[0048] The coating X is obtained through the following steps:
[0049] The metal oxide carrier is immersed in an aqueous solution containing a noble metal element precursor and an auxiliary agent precursor, then dried and calcined to obtain the coating X.
[0050] The aqueous solution containing the noble metal element precursor and the auxiliary agent precursor
[0051] The concentration of the noble metal element precursor is 0.2–10 wt%.
[0052] Optionally, the concentration of the noble metal element precursor is any value among 0.2wt%, 1wt%, and 10wt%, or any value between two of them.
[0053] The concentration of the auxiliary agent precursor is 0.1–10 wt%.
[0054] Optionally, the concentration of the auxiliary precursor is any value among 0.1 wt%, 1 wt%, 5 wt%, and 10 wt%, or any range between both.
[0055] The solid-liquid ratio of the metal oxide support to the aqueous solution containing the noble metal element precursor and the auxiliary precursor is (0.5-2):1 g / ml;
[0056] The coating Y is obtained through the following steps:
[0057] The metal oxide support is immersed in an aqueous solution containing a transition metal oxide precursor, dried, and calcined to obtain the coating Y;
[0058] In the aqueous solution containing the transition metal oxide precursor, the concentration of the transition metal oxide precursor is 0.2–50 wt%.
[0059] Optionally, in the aqueous solution containing the transition metal oxide precursor, the concentration of the transition metal oxide precursor is any value or a range between 0.2 wt%, 1 wt%, 10 wt%, 20 wt%, 30 wt%, 40 wt%, and 50 wt%.
[0060] The solid-liquid ratio of the metal oxide support to the aqueous solution containing the transition metal oxide precursor is (0.5-2):1 g / ml.
[0061] Optionally, the solid-liquid ratio of the metal oxide support to the aqueous solution containing the transition metal oxide precursor is any value among 0.5:1 g / ml, 1:1 g / ml, and 2:1 g / ml, or any range between the two.
[0062] The coating Z is obtained through the following steps:
[0063] The metal oxide carrier is immersed in an aqueous solution containing a noble metal element precursor and a transition metal oxide precursor, then dried and calcined to obtain the coating Z.
[0064] The aqueous solution containing noble metal element precursors and transition metal oxide precursors
[0065] The concentration of the noble metal element precursor is 0.3–10 wt%.
[0066] Optionally, the concentration of the noble metal element precursor is any value among 0.3wt%, 1wt%, 5wt%, and 10wt%, or any value between both.
[0067] The concentration of the transition metal oxide precursor is 0.2–50 wt%.
[0068] Optionally, the concentration of the transition metal oxide precursor is any value from 0.2wt%, 1wt%, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, or any range between the two.
[0069] The solid-liquid ratio of the metal oxide support to the aqueous solution containing the noble metal element precursor and the transition metal oxide precursor is (0.5-2):1 g / ml;
[0070] The solid-liquid ratio of the metal oxide support to the aqueous solution containing the noble metal element precursor and the transition metal oxide precursor is any value among 0.5:1 g / ml, 1:1 g / ml, and 2:1 g / ml, or any range between the two.
[0071] The noble metal element precursor is selected from at least one of platinum nitrate, chloroplatinic acid, palladium nitrate, chloropalladium acid, osmium chloride, chloroiridium acid, ruthenium chloride, and rhodium chloride.
[0072] The auxiliary agent precursor is selected from at least one of cobalt nitrate, lanthanum nitrate, potassium hydroxide, barium nitrate, tin chloride, calcium nitrate, and zinc nitrate.
[0073] The transition metal oxide precursor is selected from at least one of ferric nitrate, cobalt nitrate, ammonium molybdate, tin chloride, chromium nitrate, copper nitrate, nickel nitrate, manganese nitrate, ammonium metavanadate, and ammonium paratungstate.
[0074] The drying temperature is 80–150°C;
[0075] Optionally, the drying temperature is any value among 80°C, 100°C, and 150°C, or a range between any two.
[0076] The drying time is 1 to 24 hours;
[0077] Optionally, the drying time is any value among 1h, 6h, 12h, 18h, and 24h, or a range between any two.
[0078] The calcination temperature is 400–800℃;
[0079] Optionally, the calcination temperature is any value among 400℃, 500℃, 600℃, 700℃, and 800℃, or a range between any two.
[0080] The calcination time is 1 to 8 hours.
[0081] Optionally, the calcination time is any value among 1h, 2h, 3h, 4h, 5h, 6h, 7h, and 8h, or a range between any two.
[0082] The process of preparing coatings X, Y, and Z into corresponding coating slurries x, y, and z includes the following steps:
[0083] One of coatings X, Y, and Z is mixed with an adhesive, a surfactant, a pH adjuster, and water. The pH is adjusted to 1–7, and the mixture is ball-milled to obtain the corresponding coating slurry x, coating slurry y, or coating slurry z.
[0084] The adhesive is selected from at least one of silica sol, aluminum sol, titanium sol, and zirconium sol;
[0085] The ratio of one of the coatings X, Y, and Z to the adhesive is 1:0.5 to 1:0.05;
[0086] The surfactant is selected from at least one of polyethylene glycol, glycerol, carboxymethyl cellulose, polyvinyl alcohol, and polyacryl alcohol;
[0087] The ratio of one of the coatings X, Y, and Z to the surfactant is 1:(0.02~0.001);
[0088] Optionally, the ratio of one of the coatings X, Y, and Z to the surfactant is any value from 1:0.02, 1:0.01, 1:0.005, 1:0.001, or any range between two of them.
[0089] The ratio of one of the coatings X, Y, and Z to the water is 1:(1-7);
[0090] The ratio of one of the coatings X, Y, and Z to the water is any value from 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, or any range between the two.
[0091] The pH adjuster is selected from acids and / or bases;
[0092] The acid is selected from at least one of formic acid, acetic acid, hydrochloric acid, citric acid, phosphoric acid, and nitric acid;
[0093] The alkali is selected from at least one of ammonia, sodium carbonate, and sodium hydroxide.
[0094] The rotational speed of the ball mill is 200–500 r / min;
[0095] Optionally, the rotational speed of the ball mill is any value among 200 r / min, 300 r / min, 400 r / min, and 500 r / min, or a range between any two.
[0096] The ball milling time is 1 to 20 hours.
[0097] Optionally, the ball milling time is any value among 1h, 5h, 10h, 15h, and 20h, or a range between any two.
[0098] The calcination temperature is 400–800°C;
[0099] Optionally, the roasting temperature is any value among 400℃, 500℃, 600℃, 700℃, and 800℃, or a range between any two.
[0100] The roasting time is 1 to 10 hours;
[0101] Optionally, the roasting time is any value among 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, and 10h, or a range between any two.
[0102] The reduction temperature is 350–550°C;
[0103] Optionally, the reduction temperature is any value among 350°C, 400°C, 450°C, and 550°C, or a range between any two.
[0104] The reduction time is 1 to 4 hours;
[0105] Optionally, the restoration time is any value among 1h, 2h, 3h, and 4h, or a range between any two.
[0106] The reducing atmosphere is a hydrogen atmosphere;
[0107] Optionally, the hydrogen atmosphere also contains nitrogen.
[0108] Specifically,
[0109] The substrate of the hydrogen sulfide-containing VOCs gas purification catalyst adopts an integral honeycomb carrier. At least two layers of catalytic material are coated on the substrate surface. The first catalytic material layer (coating X of coating I) is coated on the substrate surface and includes a metal oxide support and platinum group metals (noble metal elements) as active components. The second catalytic material layer is coated on the surface of the first catalytic material layer. The second layer is divided into two regions according to the gas flow direction. The catalytic material in the first region (coating Y of region a) consists of a metal oxide support and transition metal oxides. The catalytic material in the second region (coating Z of region a) consists of a metal oxide support, transition metal oxides, and platinum group metals. In the first region of the second coating layer, a hydrogen sulfide-hydrogenation reaction occurs to generate sulfur dioxide, ensuring that sulfur in the reaction gas entering the first coating layer exists in the form of sulfur dioxide. Since the platinum group metals in the first layer are resistant to sulfur dioxide, this protects the platinum group metals from poisoning caused by hydrogen sulfide. In the second region of the second coating layer, a reaction occurs to oxidize the hydrogen sulfide converted in the first region to sulfur dioxide, while simultaneously, a VOCs catalytic oxidation reaction occurs in the first coating layer.
[0110] The preparation method includes the following steps:
[0111] Preparation of catalytic materials:
[0112] Material X is prepared by immersing an aqueous solution of a platinum group metal precursor onto a metal oxide support, drying it at 80–150 °C, and calcining it at 400–800 °C for 1–8 h.
[0113] Material Y is prepared by immersing an aqueous solution of a transition metal oxide precursor onto a metal oxide support, drying it at 80–150 °C, and calcining it at 400–800 °C for 1–8 h.
[0114] Material Z is prepared by immersing an aqueous solution of platinum group metal and transition metal oxide precursors onto a metal oxide support, drying at 80–150°C, and calcining at 400–800°C for 1–8 hours.
[0115] Preparation of coating slurry:
[0116] The prepared material X, binder, surfactant, and pH adjuster are added to deionized water to adjust the pH to between 1 and 7. The mixture is then added to a ball mill jar and ball milled for 1 to 20 hours at a speed of 200 to 500 r / min to obtain coating slurry X.
[0117] The prepared material Y, binder, surfactant, and pH adjuster are added to deionized water to adjust the pH to between 1 and 7. The mixture is then added to a ball mill jar and ball-milled for 1 to 20 hours at a speed of 200 to 500 r / min to obtain the coating slurry y.
[0118] The prepared material Z, binder, surfactant, and pH adjuster are added to deionized water to adjust the pH to between 1 and 7. The mixture is then added to a ball mill jar and ball-milled for 1 to 20 hours at a speed of 200 to 500 r / min to obtain the coating slurry Z.
[0119] Coating preparation: The entire honeycomb carrier is immersed in slurry x, and excess slurry liquid in the pores of the honeycomb carrier is blown out with compressed air; then, the honeycomb carrier coated with oxide coating is microwave-dried for 1-15 min, and the above process is repeated until the designed loading is reached, to obtain a honeycomb carrier with the first layer of coating; the honeycomb carrier with the first layer of coating is partially immersed in slurry y according to the designed loading, and excess slurry liquid in the pores of the honeycomb carrier is blown out with compressed air; then, the honeycomb carrier coated with oxide coating is microwave-dried for 1-15 min, and the above process is repeated until the designed loading is reached, to obtain a honeycomb carrier with the second layer of first region coating; the honeycomb carrier with the second layer of first region coating is partially immersed in slurry z according to the designed loading, and excess slurry liquid in the pores of the honeycomb carrier is blown out with compressed air; then, the honeycomb carrier coated with oxide coating is microwave-dried for 1-15 min, and the above process is repeated until the designed loading is reached, to obtain a honeycomb carrier with the second layer of second region coating, and calcined at 400-800℃ for 1-10 hours to obtain the integral structure catalyst;
[0120] Catalyst reduction: Reduction at 450°C for 1–4 hours under an atmosphere of 10 vol.% H2–90 vol.% N2.
[0121] The catalyst has a second layer of catalytic material, which is divided into two regions: the first region is located on the gas inlet side and the second region is located on the gas outlet side.
[0122] According to another aspect of this application, a hydrogen sulfide-containing VOCs gas purification catalyst is provided, comprising the above-described layered composite material or the layered composite material prepared by the above-described preparation method.
[0123] According to another aspect of this application, a method for purifying hydrogen sulfide-containing VOCs gas is provided, using the aforementioned hydrogen sulfide-containing VOCs gas purification catalyst.
[0124] The hydrogen sulfide-containing VOCs gas first comes into contact with region a, and then with region b.
[0125] The hydrogen sulfide-containing VOCs gas purification catalyst of the present invention has the following advantages:
[0126] The hydrogen sulfide-containing VOCs gas purification catalyst of the present invention has high catalytic activity and stability under high space velocity conditions;
[0127] The hydrogen sulfide-containing VOCs gas purification catalyst of the present invention has good hydrogen sulfide resistance, low catalyst resistance drop, and long service life.
[0128] The hydrogen sulfide-containing VOCs gas purification catalyst of the present invention has a simple preparation process and low manufacturing cost. Attached Figure Description
[0129] Figure 1 : This is a schematic diagram of the catalyst coating partition obtained in Example 1 of this application.
[0130] Figure 2 Stability evaluation of the catalysts obtained in the comparative example under SO2 and H2S conditions.
[0131] Figure 3 Stability evaluation of the catalyst obtained in Example 1.
[0132] Figure 4 Stability evaluation of the catalyst obtained in Example 1 and the catalyst obtained in the comparative example. Detailed Implementation
[0133] The present invention will be described in detail below. The following are only preferred embodiments of the present invention and should not be construed as limiting the scope of the present invention.
[0134] Example 1:
[0135] 50g of titanium dioxide was weighed and impregnated in an aqueous solution containing 0.41g of platinum nitrate and 0.27g of lanthanum nitrate hexahydrate, dried at 120℃ for 12h, and calcined at 500℃ for 4h to obtain catalyst A; 50g of titanium dioxide was weighed and impregnated in an aqueous solution containing 23.8g of ferric nitrate nonahydrate, dried at 120℃ for 12h, and calcined at 500℃ for 4h to obtain catalyst B; 50g of titanium dioxide was weighed and impregnated in an aqueous solution containing 0.22g of platinum nitrate and 23.8g of ferric nitrate nonahydrate, dried at 120℃ for 12h, and calcined at 500℃ for 4h to obtain catalyst C. Weigh 50g of catalyst material A, 20g of silica sol, 0.3ml of concentrated nitric acid, and 0.5g of polyethylene glycol and add them to 120g of deionized water, with a pH of 2-4. Add this mixture to a ball mill jar and ball mill at 500 rpm for 4 hours to obtain coating slurry D. Weigh 50g of catalyst material B, 20g of silica sol, 0.5ml of concentrated nitric acid, and 0.5g of polyethylene glycol and add them to 120g of deionized water, with a pH of 2-4. The mixture was added to a ball mill jar and milled for 4 hours at 500 rpm to obtain coating slurry E. 50g of catalyst material C, 20g of silica sol, 0.3ml of concentrated nitric acid, and 0.5g of polyethylene glycol were weighed and added to 120g of deionized water (pH 2-4). This mixture was then added to a ball mill jar and milled for 4 hours at 500 rpm to obtain coating slurry F. A 200-mesh honeycomb ceramic carrier was immersed in coating slurry D. Excess slurry in the pores of the honeycomb carrier is blown out with compressed air; then microwave dried for 5 minutes. This process is repeated until the coating mass accounts for 10%–12% of the total mass of the honeycomb carrier before coating, completing the loading of the first coating layer. Half of the carrier coated with the first coating layer is immersed in the coating slurry E, and excess slurry in the pores of the honeycomb carrier is blown out with compressed air; then microwave dried for 5 minutes. This process is repeated until the coating mass accounts for 5%–6% of the total mass of the honeycomb carrier before coating, completing the loading of the second layer, first region coating. The other half of the carrier coated with the second layer, first region coating, is immersed in the coating slurry F, and excess slurry in the pores of the honeycomb carrier is blown out with compressed air; then microwave dried for 5 minutes. This process is repeated until the coating mass accounts for 5%–6% of the total mass of the honeycomb carrier before coating, completing the loading of the second layer, second region coating. The catalyst is then calcined at 500°C for 4 hours to obtain the monolithic catalyst. The obtained catalyst is reduced at 450°C for 2 hours under a 10 vol.% H2–90 vol.% N2 atmosphere to obtain the reduced monolithic catalyst.
[0136] Figure 1 : This is a schematic diagram of the catalyst coating partition obtained in Example 1 of this application.
[0137] Example 2:
[0138] 50g of alumina was weighed and impregnated in an aqueous solution containing 0.41g of platinum nitrate and 0.36g of zinc nitrate hexahydrate. The solution was dried at 120℃ for 12 hours and calcined at 500℃ for 4 hours to obtain catalyst A. 50g of titanium dioxide was weighed and impregnated in an aqueous solution containing 23.8g of ferric nitrate nonahydrate. The solution was dried at 120℃ for 12 hours and calcined at 500℃ for 4 hours to obtain catalyst B. 50g of alumina was weighed and impregnated in an aqueous solution containing 0.22g of platinum nitrate and 23.8g of ferric nitrate nonahydrate. The solution was dried at 120℃ for 12 hours and calcined at 500℃ for 4 hours to obtain catalyst C. Weigh 50g of catalyst material A, 20g of aluminum sol, 2.2ml of concentrated nitric acid, and 0.5g of polyvinyl alcohol and add them to 120g of deionized water, with a pH of 2-4. Add this mixture to a ball mill jar and ball mill at 500 rpm for 4 hours to obtain coating slurry D. Weigh 50g of catalyst material B, 20g of silica sol, 0.5ml of concentrated nitric acid, and 0.5g of polyethylene glycol and add them to 120g of deionized water, with a pH of 2-4. The mixture was added to a ball mill jar and ball-milled for 4 hours at 500 rpm to obtain coating slurry E. 50 g of catalyst material C, 20 g of aluminum sol, 2.2 ml of concentrated nitric acid, and 0.5 g of polyvinyl alcohol were weighed and added to 120 g of deionized water (pH 2-4). This mixture was then added to a ball mill jar and ball-milled for 4 hours at 500 rpm to obtain coating slurry F. A 200-mesh honeycomb ceramic carrier was immersed in coating slurry D. Excess slurry in the pores of the honeycomb carrier is blown out with compressed air; then microwave dried for 5 minutes. This process is repeated until the coating mass accounts for 10%–12% of the total mass of the honeycomb carrier before coating, completing the loading of the first coating layer. Half of the carrier coated with the first coating layer is immersed in the coating slurry E, and excess slurry in the pores of the honeycomb carrier is blown out with compressed air; then microwave dried for 5 minutes. This process is repeated until the coating mass accounts for 5%–6% of the total mass of the honeycomb carrier before coating, completing the loading of the second layer, first region coating. The other half of the carrier coated with the second layer, first region coating, is immersed in the coating slurry F, and excess slurry in the pores of the honeycomb carrier is blown out with compressed air; then microwave dried for 5 minutes. This process is repeated until the coating mass accounts for 5%–6% of the total mass of the honeycomb carrier before coating, completing the loading of the second layer, second region coating. The catalyst is then calcined at 500°C for 4 hours to obtain the monolithic catalyst. The obtained catalyst is reduced at 450°C for 2 hours under a 10 vol.% H2-90 vol.% N2 atmosphere to obtain the reduced monolithic catalyst.
[0139] Example 3:
[0140] 50g of zirconium oxide was weighed and impregnated in an aqueous solution containing 0.41g of platinum nitrate and 0.27g of lanthanum nitrate hexahydrate, dried at 120℃ for 12h, and calcined at 500℃ for 4h to obtain catalyst A; 50g of titanium dioxide was weighed and impregnated in an aqueous solution containing 23.8g of ferric nitrate nonahydrate, dried at 120℃ for 12h, and calcined at 500℃ for 4h to obtain catalyst B; 50g of zirconium oxide was weighed and impregnated in an aqueous solution containing 0.22g of platinum nitrate and 23.8g of ferric nitrate nonahydrate, dried at 120℃ for 12h, and calcined at 500℃ for 4h to obtain catalyst C. Weigh 50g of catalyst material A, 20g of zirconium sol, 0.5ml of concentrated nitric acid, and 0.5g of polyethylene glycol and add them to 120g of deionized water, with a pH of 2-4. Add this mixture to a ball mill jar and ball mill at 500 rpm for 4 hours to obtain coating slurry D. Weigh 50g of catalyst material B, 20g of silica sol, 0.5ml of concentrated nitric acid, and 0.5g of polyethylene glycol and add them to 120g of deionized water, with a pH of 2-4. The mixture was added to a ball mill jar and milled for 4 hours at 500 rpm to obtain coating slurry E. 50g of catalyst material C, 20g of zirconium sol, 0.5ml of concentrated nitric acid, and 0.5g of polyethylene glycol were weighed and added to 120g of deionized water (pH 2-4). This mixture was then added to a ball mill jar and milled for 4 hours at 500 rpm to obtain coating slurry F. A 200-mesh honeycomb ceramic carrier was immersed in coating slurry D. Excess slurry in the pores of the honeycomb carrier is blown out with compressed air; then microwave dried for 5 minutes. This process is repeated until the coating mass accounts for 10%–12% of the total mass of the honeycomb carrier before coating, completing the loading of the first coating layer. Half of the carrier coated with the first coating layer is immersed in the coating slurry E, and excess slurry in the pores of the honeycomb carrier is blown out with compressed air; then microwave dried for 5 minutes. This process is repeated until the coating mass accounts for 5%–6% of the total mass of the honeycomb carrier before coating, completing the loading of the second layer, first region coating. The other half of the carrier coated with the second layer, first region coating, is immersed in the coating slurry F, and excess slurry in the pores of the honeycomb carrier is blown out with compressed air; then microwave dried for 5 minutes. This process is repeated until the coating mass accounts for 5%–6% of the total mass of the honeycomb carrier before coating, completing the loading of the second layer, second region coating. The catalyst is then calcined at 500°C for 4 hours to obtain the monolithic catalyst. The obtained catalyst is reduced at 450°C for 2 hours under a 10 vol.% H2-90 vol.% N2 atmosphere to obtain the reduced monolithic catalyst.
[0141] Example 4:
[0142] 50g of titanium dioxide was weighed and impregnated in an aqueous solution containing 0.41g of platinum nitrate and 0.27g of lanthanum nitrate hexahydrate. The mixture was dried at 120℃ for 12h and calcined at 500℃ for 4h to obtain catalyst A. 50g of titanium dioxide was weighed and impregnated in an aqueous solution containing 18.1g of cobalt nitrate hexahydrate. The mixture was dried at 120℃ for 12h and calcined at 500℃ for 4h to obtain catalyst B. 50g of titanium dioxide was weighed and impregnated in an aqueous solution containing 0.22g of platinum nitrate and 18.1g of cobalt nitrate hexahydrate. The mixture was dried at 120℃ for 12h and calcined at 500℃ for 4h to obtain catalyst C. Weigh 50g of catalyst material A, 20g of silica sol, 0.3ml of concentrated nitric acid, and 0.5g of polyethylene glycol and add them to 120g of deionized water, with a pH of 2-4. Add this mixture to a ball mill jar and ball mill at 500 rpm for 4 hours to obtain coating slurry D. Weigh 50g of catalyst material B, 20g of silica sol, 0.3ml of concentrated nitric acid, and 0.5g of polyethylene glycol and add them to 120g of deionized water, with a pH of 2-4. The mixture was added to a ball mill jar and milled for 4 hours at 500 rpm to obtain coating slurry E. 50g of catalyst material C, 20g of silica sol, 0.3ml of concentrated nitric acid, and 0.5g of polyethylene glycol were weighed and added to 120g of deionized water (pH 2-4). This mixture was then added to a ball mill jar and milled for 4 hours at 500 rpm to obtain coating slurry F. A 200-mesh honeycomb ceramic carrier was immersed in coating slurry D. Excess slurry in the pores of the honeycomb carrier is blown out with compressed air; then microwave dried for 5 minutes. This process is repeated until the coating mass accounts for 10%–12% of the total mass of the honeycomb carrier before coating, completing the loading of the first coating layer. Half of the carrier coated with the first coating layer is immersed in the coating slurry E, and excess slurry in the pores of the honeycomb carrier is blown out with compressed air; then microwave dried for 5 minutes. This process is repeated until the coating mass accounts for 5%–6% of the total mass of the honeycomb carrier before coating, completing the loading of the second layer, first region coating. The other half of the carrier coated with the second layer, first region coating, is immersed in the coating slurry F, and excess slurry in the pores of the honeycomb carrier is blown out with compressed air; then microwave dried for 5 minutes. This process is repeated until the coating mass accounts for 5%–6% of the total mass of the honeycomb carrier before coating, completing the loading of the second layer, second region coating. The catalyst is then calcined at 500°C for 4 hours to obtain the monolithic catalyst. The obtained catalyst is reduced at 450°C for 2 hours under a 10 vol.% H2–90 vol.% N2 atmosphere to obtain the reduced monolithic catalyst.
[0143] Example 5:
[0144] 50g of alumina was weighed and impregnated in an aqueous solution containing 0.41g of platinum nitrate and 0.36g of cobalt nitrate hexahydrate. The mixture was dried at 120℃ for 12 hours and calcined at 500℃ for 4 hours to obtain catalyst A. 50g of zirconium oxide was weighed and impregnated in an aqueous solution containing 6.8g of ammonium molybdate. The mixture was dried at 120℃ for 12 hours and calcined at 500℃ for 4 hours to obtain catalyst B. 50g of alumina was weighed and impregnated in an aqueous solution containing 0.22g of platinum nitrate and 6.8g of ammonium molybdate. The mixture was dried at 120℃ for 12 hours and calcined at 500℃ for 4 hours to obtain catalyst C. Weigh 50g of catalyst material A, 20g of aluminum sol, 2.2ml of concentrated nitric acid, and 0.5g of polyvinyl alcohol and add them to 120g of deionized water, with a pH of 2-4. Add this mixture to a ball mill jar and ball mill at 500 rpm for 4 hours to obtain coating slurry D. Weigh 50g of catalyst material B, 20g of zirconium sol, 0.5ml of concentrated nitric acid, and 0.5g of polyethylene glycol and add them to 120g of deionized water, with a pH of 2-4. The mixture was added to a ball mill jar and ball-milled for 4 hours at 500 rpm to obtain coating slurry E. 50 g of catalyst material C, 20 g of aluminum sol, 2.2 ml of concentrated nitric acid, and 0.5 g of polyvinyl alcohol were weighed and added to 120 g of deionized water (pH 2-4). This mixture was then added to a ball mill jar and ball-milled for 4 hours at 500 rpm to obtain coating slurry F. A 200-mesh honeycomb ceramic carrier was immersed in coating slurry D. Excess slurry in the pores of the honeycomb carrier is blown out with compressed air; then microwave dried for 5 minutes. This process is repeated until the coating mass accounts for 10%–12% of the total mass of the honeycomb carrier before coating, completing the loading of the first coating layer. Half of the carrier coated with the first coating layer is immersed in the coating slurry E, and excess slurry in the pores of the honeycomb carrier is blown out with compressed air; then microwave dried for 5 minutes. This process is repeated until the coating mass accounts for 5%–6% of the total mass of the honeycomb carrier before coating, completing the loading of the second layer, first region coating. The other half of the carrier coated with the second layer, first region coating, is immersed in the coating slurry F, and excess slurry in the pores of the honeycomb carrier is blown out with compressed air; then microwave dried for 5 minutes. This process is repeated until the coating mass accounts for 5%–6% of the total mass of the honeycomb carrier before coating, completing the loading of the second layer, second region coating. The catalyst is then calcined at 500°C for 4 hours to obtain the monolithic catalyst. The obtained catalyst is reduced at 450°C for 2 hours under a 10 vol.% H2-90 vol.% N2 atmosphere to obtain the reduced monolithic catalyst.
[0145] Example 6:
[0146] 50g of alumina was weighed and impregnated in an aqueous solution containing 0.41g of platinum nitrate and 0.27g of lanthanum nitrate hexahydrate, dried at 120℃ for 12h, and calcined at 500℃ for 4h to obtain catalyst A. 50g of zirconium oxide was weighed and impregnated in an aqueous solution containing 19.5g of nickel nitrate hexahydrate, dried at 120℃ for 12h, and calcined at 500℃ for 4h to obtain catalyst B. 50g of alumina was weighed and impregnated in an aqueous solution containing 0.22g of platinum nitrate and 19.5g of nickel nitrate hexahydrate, dried at 120℃ for 12h, and calcined at 500℃ for 4h to obtain catalyst C. Weigh 50g of catalyst material A, 20g of aluminum sol, 2.2ml of concentrated nitric acid, and 0.5g of polyvinyl alcohol and add them to 120g of deionized water, with a pH of 2-4. Add this mixture to a ball mill jar and ball mill at 500 rpm for 4 hours to obtain coating slurry D. Weigh 50g of catalyst material B, 20g of zirconium sol, 0.5ml of concentrated nitric acid, and 0.5g of polyethylene glycol and add them to 120g of deionized water, with a pH of 2-4. The mixture was added to a ball mill jar and ball-milled for 4 hours at 500 rpm to obtain coating slurry E. 50 g of catalyst material C, 20 g of aluminum sol, 2.2 ml of concentrated nitric acid, and 0.5 g of polyvinyl alcohol were weighed and added to 120 g of deionized water (pH 2-4). This mixture was then added to a ball mill jar and ball-milled for 4 hours at 500 rpm to obtain coating slurry F. A 200-mesh honeycomb ceramic carrier was immersed in coating slurry D. Excess slurry in the pores of the honeycomb carrier is blown out with compressed air; then microwave dried for 5 minutes. This process is repeated until the coating mass accounts for 10%–12% of the total mass of the honeycomb carrier before coating, completing the loading of the first coating layer. Half of the carrier coated with the first coating layer is immersed in the coating slurry E, and excess slurry in the pores of the honeycomb carrier is blown out with compressed air; then microwave dried for 5 minutes. This process is repeated until the coating mass accounts for 5%–6% of the total mass of the honeycomb carrier before coating, completing the loading of the second layer, first region coating. The other half of the carrier coated with the second layer, first region coating, is immersed in the coating slurry F, and excess slurry in the pores of the honeycomb carrier is blown out with compressed air; then microwave dried for 5 minutes. This process is repeated until the coating mass accounts for 5%–6% of the total mass of the honeycomb carrier before coating, completing the loading of the second layer, second region coating. The catalyst is then calcined at 500°C for 4 hours to obtain the monolithic catalyst. The obtained catalyst is reduced at 450°C for 2 hours under a 10 vol.% H2-90 vol.% N2 atmosphere to obtain the reduced monolithic catalyst.
[0147] Comparative example:
[0148] 50g of alumina was weighed and impregnated in an aqueous solution containing 0.41g of platinum nitrate. The solution was dried at 120℃ for 12 hours and calcined at 500℃ for 4 hours to obtain catalyst A. 50g of catalyst A, 20g of aluminum sol, 2.2ml of concentrated nitric acid, and 0.5g of polyvinyl alcohol were weighed and added to 120g of deionized water (pH 2-4). This mixture was then added to a ball mill jar and ball-milled at 500 rpm for 4 hours to obtain coating slurry D. A 200-mesh honeycomb ceramic carrier was immersed in coating slurry D, and excess slurry was blown out of the pores of the honeycomb carrier with compressed air. The carrier was then microwave-dried for 5 minutes. This process was repeated until the coating mass accounted for 20%-22% of the total mass of the honeycomb carrier before coating, thus completing the coating loading. The carrier was then calcined at 500℃ for 4 hours to obtain the monolithic catalyst. The obtained catalyst was reduced at 450℃ for 2 hours under a 10 vol.% H2-90 vol.% N2 atmosphere to obtain the reduced monolithic catalyst.
[0149] The activity and stability of the hydrogen sulfide-containing gas purification catalysts in Examples 1-6 and the comparative examples were evaluated. The reaction gas composition was: C8H 10 (m-xylene) = 0.18%, O2 = 6%, CO2 = 8%, H2S = 34ppm, reaction space velocity 50000h -1 .
[0150] Figure 2 The reaction conditions are: C8H 10 (m-xylene) = 0.18%, O2 = 6%, CO2 = 8%, 50000h-1, SO2 is introduced into the reaction gas during the time interval of 0-22h, and SO2 is switched to H2S during the time interval of 22-42h. Figure 3 , Figure 4 The reaction conditions are: C8H 10 (m-xylene) = 0.18%, O2 = 6%, CO2 = 8%, H2S = 34ppm, 50000h -1 .
[0151] The catalyst activity and stability are shown in the table below.
[0152]
[0153] As can be seen from the table, under H2S conditions, the catalysts obtained in Examples 1-6 exhibit significantly better activity and stability for the catalytic oxidation of xylene than the catalysts obtained in the comparative examples.
[0154] Figure 2Stability evaluation of the catalysts obtained in the comparative example under SO2 and H2S conditions. The figure shows that the catalysts obtained in the comparative example exhibit good catalytic oxidation activity of m-xylene under SO2 conditions, but the catalytic activity significantly decreases when switched to H2S conditions, indicating partial deactivation under H2S conditions.
[0155] Figure 3 Stability evaluation of the catalyst obtained in Example 1. As can be seen from the figure, under H2S conditions, the catalyst obtained in Example 1 exhibits good catalytic oxidation activity and stability for m-xylene, with the m-xylene conversion still greater than 90% after 110 h of reaction.
[0156] Figure 4 Stability evaluation of the catalyst obtained in Example 1 and the catalyst obtained in the comparative example. As can be seen from the figure, under H2S conditions, the catalyst obtained in Example 1 exhibits significantly better activity and stability for the catalytic oxidation of xylene than the catalyst obtained in the comparative example.
[0157] The above description is merely a few embodiments of this application and is not intended to limit this application in any way. Although this application discloses preferred embodiments as described above, it is not intended to limit this application. Any changes or modifications made by those skilled in the art without departing from the scope of the technical solution of this application using the disclosed technical content are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A layered composite material, characterized in that, The layered composite material includes a honeycomb carrier, a coating I coated on the surface of a substrate, and a coating II coated on the surface of the coating I; The coating I contains a metal oxide carrier, a noble metal element, and additives; The coating II includes region a and region b; The coating in region a is region a coating; The coating in region b is the region b coating; The coating in region a contains a metal oxide carrier and a transition metal oxide; The coating in region b contains a metal oxide carrier, a transition metal oxide, and a noble metal element. The mass of coating I is 3-15 wt% of the mass of the cellular carrier; The mass of the coating in region a is 1.5~10 wt% of the mass of the cellular carrier; The mass of the coating in region b is 1.5~10 wt% of the mass of the cellular carrier. The metal oxide support is selected from at least one of aluminum oxide, titanium oxide, cerium oxide, zirconium oxide, yttrium oxide, neodymium oxide, tin oxide, and chromium oxide; The precious metal element is selected from at least one of platinum, palladium, osmium, iridium, ruthenium, and rhodium; The auxiliary agent is selected from at least one of cobalt oxide, lanthanum oxide, potassium oxide, barium oxide, tin oxide, calcium oxide, and zinc oxide; The transition metal oxide is selected from at least one of iron oxide, cobalt oxide, molybdenum oxide, tin oxide, chromium oxide, copper oxide, nickel oxide, manganese oxide, vanadium oxide, and tungsten oxide. In coating I: The mass content of the metal oxide support is 90~99.6 wt%; The mass content of the precious metal element is 0.3~10 wt%; The mass content of the auxiliary agent is 0.1~3wt%; In the coating of region a: The mass content of the metal oxide support is 80~99.5 wt%; The mass content of the transition metal oxide is 0.5~20wt%; The coating in region b: The mass content of the metal oxide carrier is 70~99 wt%; The mass content of the transition metal oxide is 0.5~20 wt%; The mass content of the precious metal element is 0.5~10wt%.
2. A method for preparing the layered composite material according to claim 1, characterized in that, Includes the following steps: 1) Obtain coating I with paint X; 2) Obtain the coating Y of region a; 3) Obtain the coating Z of region b; 4) Prepare coating slurry x, coating slurry y, and coating slurry z from coatings X, Y, and Z; 5) Coating is performed on a honeycomb carrier, followed by calcination and reduction to obtain the layered composite material.
3. The preparation method according to claim 2, characterized in that, The coating X is obtained through the following steps: The metal oxide carrier is immersed in an aqueous solution containing a noble metal element precursor and an auxiliary agent precursor, then dried and calcined to obtain the coating X. The aqueous solution containing the noble metal element precursor and the auxiliary agent precursor The concentration of the noble metal element precursor is 0.2~10 wt%; The concentration of the auxiliary agent precursor is 0.1~10 wt%; The solid-liquid ratio of the metal oxide support to the aqueous solution containing the noble metal element precursor and the auxiliary precursor is (0.5~2):1g / ml; The coating Y is obtained through the following steps: The metal oxide support is immersed in an aqueous solution containing a transition metal oxide precursor, dried, and calcined to obtain the coating Y; In the aqueous solution containing the transition metal oxide precursor, the concentration of the transition metal oxide precursor is 0.2~50 wt%; The solid-liquid ratio of the metal oxide support to the aqueous solution containing the transition metal oxide precursor is (0.5~2):1 g / ml; The coating Z is obtained through the following steps: The metal oxide carrier is immersed in an aqueous solution containing a noble metal element precursor and a transition metal oxide precursor, then dried and calcined to obtain the coating Z. The aqueous solution containing noble metal element precursors and transition metal oxide precursors The concentration of the noble metal element precursor is 0.3~10 wt%; The concentration of the transition metal oxide precursor is 0.2~50 wt%; The solid-liquid ratio of the metal oxide support to the aqueous solution containing the noble metal element precursor and the transition metal oxide precursor is (0.5~2):1 g / ml; The noble metal element precursor is selected from at least one of platinum nitrate, chloroplatinic acid, palladium nitrate, chloropalladium acid, osmium chloride, chloroiridium acid, ruthenium chloride, and rhodium chloride. The auxiliary agent precursor is selected from at least one of cobalt nitrate, lanthanum nitrate, potassium hydroxide, barium nitrate, tin chloride, calcium nitrate, and zinc nitrate. The transition metal oxide precursor is selected from at least one of ferric nitrate, cobalt nitrate, ammonium molybdate, tin chloride, chromium nitrate, copper nitrate, nickel nitrate, manganese nitrate, ammonium metavanadate, and ammonium paratungstate. The drying temperature is 80~150℃; The drying time is 1~24 hours; The calcination temperature is 400~800℃; The calcination time is 1 to 8 hours.
4. The preparation method according to claim 2, characterized in that, The process of preparing coatings X, Y, and Z into corresponding coating slurries x, y, and z includes the following steps: Mix one of coatings X, Y, and Z with an adhesive, a surfactant, a pH adjuster, and water, adjust the pH to 1-7, and ball mill to obtain the corresponding coating slurry x, coating slurry y, or coating slurry z. The adhesive is selected from at least one of silica sol, aluminum sol, titanium sol, and zirconium sol; The mass ratio of one of the coatings X, Y, and Z to the adhesive is 1:0.5 to 1:0.05; The surfactant is selected from at least one of polyethylene glycol, glycerol, carboxymethyl cellulose, polyvinyl alcohol, and polyacryl alcohol; The mass ratio of one of the coatings X, Y, and Z to the surfactant is 1:0.02 to 1:0.001; The mass ratio of one of the coatings X, Y, and Z to the water is 1:7 to 1:1; The pH adjuster is selected from acids and / or bases; The acid is selected from at least one of formic acid, acetic acid, hydrochloric acid, citric acid, phosphoric acid, and nitric acid; The alkali is selected from at least one of ammonia, sodium carbonate, and sodium hydroxide. The rotational speed of the ball mill is 200~500 r / min; The ball milling time is 1 to 20 hours.
5. The preparation method according to claim 2, characterized in that, The roasting temperature is 400~800℃; The roasting time is 1~10 hours; The reduction temperature is 350~550℃; The restoration time is 1-4 hours; The reducing atmosphere is a hydrogen atmosphere.
6. The preparation method according to claim 5, characterized in that, The hydrogen atmosphere also contains nitrogen.
7. A catalyst for purifying VOCs gas containing hydrogen sulfide, characterized in that... , This includes the layered composite material according to claim 1 or the layered composite material prepared by the preparation method according to any one of claims 2 to 6.
8. A method for purifying hydrogen sulfide-containing VOCs gas, characterized in that, The hydrogen sulfide-containing VOCs gas purification catalyst described in claim 7 is used.
9. The method according to claim 8, characterized in that, The hydrogen sulfide-containing VOCs gas first comes into contact with region a, and then with region b.
Citation Information
Patent Citations
Sulfur-tolerant catalyst for gas deoxidation as well as preparation method and application thereof
CN102553585A
Containing-sulphur organic catalyst to burned waste gas and its preparation
CN1049299A
Metal-matrix catalytic combustion catalyst and preparation method thereof
CN105709854A
VOCs (volatile organic chemcials) catalytic combustion integral catalyst and preparation method thereof
CN106732585A
Lean burning NOx trapping catalyst
CN110075836A